Peran Pasar Modal Syariah Dalam Meningkatkan Perekonomian Di Indonesia - Dian Puspitasari; Fitria Ayu Ningtyas; Lilik Fitria Fatmawati; Agus Eko Sujianto (Universitas Maritim AMNI Semarang, 2023)
The Islamic capital market is an alternative source of funding as well as an investment vehicle for a company whose operational activities are based on sharia principles. In this case the Islamic capital market affects the level of economic growth of a country. where when the level of investment is high, the country's economic growth will increase and vice versa. The purpose of this study is to determine the role of the Islamic capital market in increasing economic growth in Indonesia. This research uses the literature study method with sources from articles, books and data analysis using descriptive analysis regarding the role of the Islamic capital market in increasing economic growth in Indonesia. The results of the study show that Indonesia's economic growth is inseparable from the role of Islamic stock investment. Economic growth can be measured with the value of Gross Domestic Product (GDP). GDP continues to increase over the past few years, as well as the sharia stock market capitalization which is quite stable. Where is the relationship between capitalization Islamic stock market with a positive Gross Domestic Product (GDP).